Behind the Seven Veils of Inequality. What If It S All About the Struggle Within Just One Half of the Population over Just One Half of the National Income? - Palma-Penco, J (WILEY, 2019)
This article addresses three main issues: why there is such a huge diversity of disposable income inequality across the world, why there is such a deterioration of market inequality among countries of the Organization for Economic Cooperation and Development (OECD), and why inequality seems to move in waves . There are many underlying questions: does diversity reflect a variety of fundamentals, or a multiplicity of power structures and choice? Is rising market inequality the product of somehow exogenous factors (e.g., r>g), or of complex interactions between political settlements and market failures? How do we get through the veils obscuring these interactions and distorting our vision of the often self-constructed nature of inequality? Has neoliberal globalization broadened the scope for distributional failures by, for example, triggering a process of reverse catching-up in the OECD, so that highly unequal middle-income countries like those in Latin America now embody the shape of things to come? Are we all converging towards features such as mobile elites creaming off the rewards of economic growth, and magic realist politics that lack self-respect if not originality? Should I say, Welcome to the Third World ? In this paper I also develop a new approach for examining and measuring inequality (distance from distributive targets), and a new concept of distributional waves . The article concludes that, to understand current distributive dynamics, what matters is to comprehend the forces determining the share of the rich - and, in terms of growth, what they choose to do with it (and how they are allowed do it).